AN ANALYSIS ON THE STUDENTS’ ARGUMENTATIVE COMPOSITION COMPETENCE - Samsul Amri (Program Studi Pendidikan Bahasa Inggris Fakultas Keguruan dan Ilmu Pendidikan, 2017)
Analysis on writing competence has been being interesting issue to reserach in order to gain more effective and accurate conclusion. One of the issues was on academic writing, argumentative essay composition. This current inqury aimed at investigating to what extent the students’ argumentative essay compostion competence. On the shake of the pupose, it was designed as survey research, which took 30 students of the fifth semester of English Study Program of FKIP – UNISI Tembilahan as the participants. They were asked for writing an argumenttaive essay. The indicators assessment involved format, mechanics, contents, oganization and grammar. After analyzing the data, the results revealed that the students’ competence on each of writing aspect was extremely varied. Some students could achieved maximum score, yet others could not. It was proven from the findings that there were five students (16.66%) who achieved very good classification, thirteen students (43.33%) were placed in good level, and twelve students (40%) were categorized in enough level. Overall, their competence was in level enough to very good level. It is suggested that they need to improve their performance to get better results.